A model for phosphocreatine resynthesis - Nevill, A.M.a d , Jones, D.A.b , McIntyre, D.b , Bogdanis, G.C.c , Nevill, M.E.c (Journal of Applied Physiology, 1997)
A model for phosphocreatine (PCr) resynthesis is proposed based on a simple electric circuit, where the PCr store in muscle is likened to the stored charge on the capacitor. The solution to the second-order differential equation that describes the potential around the circuit suggests the model for PCr resynthesis is given by PCr(t) = R - [d1 · exp(-k1·t) ± d2·exp(-k2·t)], where R is PCr concentration at rest, d1, d2, k1, and k2 are constants, and t is time. By using nonlinear least squares regression, this double-exponential model was shown to fit the PCr recovery data taken from two studies involving maximal exercise accurately. In study 1, when the muscle was electrically stimulated while occluded, PCr concentrations rose during the recovery phase to a level above that observed at rest. In study 2, after intensive dynamic exercise, PCr recovered monotonically to resting concentrations. The second exponential term in the double-exponential model was found to make a significant additional contribution to the quality of fit in both study 1 (P < 0.05) and study 2 (P < 0.01).